Impairment of human NK cell cytotoxic activity and cytokine release by cigarette smoke - Mian, M. Firoz; Lauzon, Nicole M.; Stämpfli, Martin R.; Mossman, Karen L.; Ashkar, Ali A. (Journal of leukocyte biology, 2008)
NK cells play essential roles in innate host defense against microbial infections and tumor surveillance. Although evidence suggests that smoking has adverse effects on the immune system, little is known about whether smoking compromises NK cell effector functions. In this study, we show that cigarette smoke‐conditioned medium (SCM) dose‐dependently inhibits in vitro IFN‐γ production by polyinosinic:polycytidylic acid (poly I:C)‐activated PBMC and NK cells isolated from nonsmoking individuals. Similarly, SCM attenuated poly I:C‐induced TNF‐α production by PBMC and NK cells. The inhibitory effect of cigarette smoke on TNF‐α production was reversible. PBMC and NK cells isolated from smokers displayed significant reduction of IFN‐γ and TNF‐α secretions compared with nonsmokers in response to poly I:C activation. We further observed that SCM attenuated NK cell cytotoxic activity, which was associated with decreased up‐regulation of perforin expression. Attenuated cytotoxic activity was also observed in PBMCs isolated from smokers. Finally, anti‐IL‐12 mAb‐blocking data revealed that an attenuation of IFN‐γ production by PBMC was indirect, likely via attenuation of IL‐12 production, and the effect on NK cells was IL‐12‐independent. Our data indicate that cigarette smoke compromises function of human NK cells. This may contribute to a higher incidence of viral infections and cancer among smokers.